BUILDING THE FUTURE OF EDUCATION: INNOVATIONS AND CHALLENGESIN TEACHER CERTIFICATION IN INDONESIA - Istiqomah Nur Rahmawati (Adisam Publisher, 2024)
The future development of education in Indonesia is very dependent on innovation and solving challenges in teacher certification. Teacher certification is a crucial step in ensuring quality and sustainable education. Building the future of education in Indonesia through innovation in teacher certification will not only improve the quality of teaching, but also increase student academic achievement and the global competitiveness of the country's education. It is important to continue to respond to emerging challenges with innovative and sustainable solutions, in line with societal needs and global educational developments. To build a better educational future, innovation in the teacher certification process is very important. One of the main challenges in teacher certification in Indonesia is ensuring that the process is fair, transparent and in line with the evolving needs of the world of education. Apart from technological innovation, collaboration between educational institutions, government and industry can also be key in building a better future for teacher certification. This collaboration can ensure that teacher certification is not just according to academic criteria, but also considering practical needs in the field, as well as preparing teachers for the challenges they may face in the real world. With innovation and strong collaboration, it is hoped that the future of teacher certification in Indonesia will be able to create quality teaching staff, ready to face complex educational challenges, and encourage educational progress throughout the country.